Heat Transfer Augmentation and Friction Factor Due to the Arrangement of Rectangular Turbulators in a Finned Air Channel of a Solar Air Heater - Byeong-Hwa An; Kwang-Hwan Choi; Hwi-Ung Choi (Energies, 2023)
In this study, the heat transfer augmentation and friction factor of a novel type of solar air heater (SAH), which incorporates longitudinal fins and rectangular turbulators, were investigated numerically with different arrangements of the turbulators. The effects of arrangements of rectangular turbulators placed in a finned air channel on its heat transfer augmentation and friction factor are discussed for Reynolds numbers ranging from 3000 to 15,000 using commercial ANSYS 17.2 software. Four different arrangements are investigated, including Array A, which places turbulators on both the fin’s side and base surfaces at the same position; Array B, where turbulators are sequentially placed on the fin’s side and base surfaces; Array C, where turbulators are only placed on the side surface; and Array D, where turbulators are placed only on the base surface. Array A showed the highest heat transfer augmentation and friction factor among the investigated arrangements. However, the highest thermo-hydraulic performance (THP), considering both the heat transfer augmentation and friction factor, was obtained in Array B, with a value of 1.36. Consequently, Array B was regarded as the most appropriate and effective arrangement method for the finned air channel of a SAH.